VD_FINDINFO HC / 2022 / 873 vom 8. Dezember 2022 - VD Tribunal cantonal (2022)
CHARGE FONCIÈRE, SERVITUDE, INTERPRÉTATIONPROCÉDURE, INTERPRÉTATIONSENS GÉNÉRAL | 730 CC, 737 CC, 738 CC, 741 CC, 312 al. 1 CPC (CH)